2013
DOI: 10.1016/j.ijproman.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the health and safety influence of subcontracting in construction: The approach of main contractors

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractSubcontracting is noted for its adverse health and safety (H&S) influence in construction.Using interviews with five of the top 20 UK contractors and one medium-sized contractor, this study explored how main contractors manage the H&S influence of subcontracting with a focus on their in-house measures. Some in-house measures found are: restricting the laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…A recent inquiry exposed the practice of blacklisting construction workers for being vocal about OSH issues (House of Commons, 2015). It is an industry highly vulnerable to economic pressure, employment fluctuates with recession and growth, hence the use of contracting to provide flexibility of labour and meet changing market demands (Manu et al, 2013). It has been suggested that, because HRO developed in non-profit organisations where safety is a primary objective, its constructs would be difficult to implement in sectors, like construction, with conflicting goals and pressures (Tamuz and Harrison, 2006).…”
Section: Culturementioning
confidence: 99%
See 1 more Smart Citation
“…A recent inquiry exposed the practice of blacklisting construction workers for being vocal about OSH issues (House of Commons, 2015). It is an industry highly vulnerable to economic pressure, employment fluctuates with recession and growth, hence the use of contracting to provide flexibility of labour and meet changing market demands (Manu et al, 2013). It has been suggested that, because HRO developed in non-profit organisations where safety is a primary objective, its constructs would be difficult to implement in sectors, like construction, with conflicting goals and pressures (Tamuz and Harrison, 2006).…”
Section: Culturementioning
confidence: 99%
“…However, this is difficult in construction because the majority of work is subcontracted, allowing firms to employ specialists on a flexible basis. As a result, the organisation becomes fragmented into units with conflicting interests, ambiguous responsibilities, inadequate communication, and reduced teamwork (Manu et al, 2013). …”
Section: Empowermentmentioning
confidence: 99%
“…This entrenched nature of subcontracting in the construction sector is partly due to the specialist nature of most construction works (Yik et al, 2006) and the strategic choice by large construction firms to emphasise flexibility as a source of competitive advantage (Winch, 1998). Manu et al (2013b) indicated that the reasons for prominence of subcontracting practice in construction are the ability to fine-tune labour flexibility, bargain down labour cost, encourage quicker completion of tasks, externalise less rewarding and dangerous activities, transfer financial risk, avoid workers' compensation cost, and rapidly meet changing product market demands. Despite the undisputed contribution of subcontracting to organisational and managerial flexibility as well as provision of specialised services, the management of relationships between main contractors and subcontractors during projects can be quite complex and problematic.…”
Section: Subcontracting and Its Ramificationsmentioning
confidence: 99%
“…Rates of work-related injuries in the construction sector are much higher than in many other areas, as has been documented in various studies and reports (Agilés-Bosch et al, 2014;Chi and Han, 2013;Fung et al, 2010;Manu et al, 2013;Martinez Aires et al, 2010;Montero et al, 2009) and so companies in this field are exposed to the high costs associated with such accidents. These costs are diverse in nature, and include human costs (which are not directly quantifiable) and financial, for the companies in the industry and for society as a whole (sick leave, medical treatment, etc.)…”
Section: Introductionmentioning
confidence: 91%